Double-armed and tetra-armed cyclen-based cryptands. Issue 5 (4th May 2017) - Ikeda, Mari; Sah, Ajay Kumar; Iwase, Miki; Murashige, Rina; Kuwahara, Shunsuke; Habata, Yoichi
Abstract: Double-armed and tetra-armed cyclen-based cryptands (1a –1d and2 ) that bridge two aromatic rings by diethyleneoxy and triethyleneoxy units were prepared. The CSI-MS of 1:1 mixtures ([Ag + ]/[ligand]) indicated that these new cryptands form 1:1 complexes with Ag + . The log K values for the interaction between Ag + and2 was greater than those of1a –1d, double-armed cyclens (3a –3c and4 ), and tetra-armed cyclen (5 ). The Ag + -ion-induced 1 H NMR spectral changes suggest that the Ag + – π interactions of the Ag + complexes with the cryptands (1a –1d and2 ) are stronger than those in Ag + /double-armed and tetra-armed cyclens. To visualise the Ag + − π interactions, the isosurfaces of the LUMO and HOMOs of the Ag + complexes were calculated at the B3LYP/3–21G(*) theoretical level. The LUMO of the Ag + ion is distorted by interaction with the HOMOs of the aromatic side arms. The calculations reveal Ag + − π interactions between the Ag + ion and the aromatic side arms, and these are shown graphically. Abstract :